The Sniffin' Sticks Odor Discrimination Memory Test: A Rapid, Easy-to-Use, Reusable Procedure for Testing Olfactory Memory - Besser, Gerold; Jobs, Leandra; Liu, David Tianxiang; Mueller, Christian A.; Renner, Bertold (Annals of Otology Rhinology and Laryngology, 2018)
OBJECTIVES:: Neurodegenerative diseases can alter odor memory in addition to inducing quantitative impairment, and olfactory memory can be tested using the validated olfactory memory test with encapsulated odors (Odor Discrimination Memory Test [ODMT]). The aim of this study was to investigate the new Sniffin' Sticks ODMT (SSODMT), which is comparable with the ODMT. METHODS:: The SSODMT was administered to 48 subjects (30 women, 18 men; mean age, 34.6 ± 16.3 years). Olfactory function was assessed using the 16-item Sniffin' Sticks Identification Test. The ODMT was administered to a subgroup of 10 subjects to assess the comparability of the SSODMT and the ODMT. Test-retest reliability was studied in another 20 subjects (10 women, 10 men; mean age, 32.9 ± 16.4 years). RESULTS:: The mean SSODMT score was 10.7 ± 1.8 (range, 5-12). SSODMT test scores were significantly correlated with Sniffin' Sticks Identification Test scores ( r67 = 0.66, P < .001) and were significantly negatively correlated with subject age ( r48 = -0.70, P < .001). SSODMT and ODMT scores were highly and significantly correlated, indicating that the test results were comparable ( r10 = 0.75, P < .05). Test-retest analysis revealed a significant correlation ( r20 = 0.68, P < .001). CONCLUSIONS:: These results demonstrate the usefulness of the new SSODMT and its comparability with the ODMT. The SSODMT is an easy, rapid, and low-cost tool that is suitable for routine use in evaluating odor memory.
EVALuna2:213547